Peak human : what we can learn from the rise and fall of golden ages - Norberg, Johan, 1973- (Atlantic Books, 2025)
"All golden ages are marked by periods of spectacular cultural flourishing, scientific exploration, technological achievement and economic growth; yet no two are the same. Their beliefs, societies and place in the wider world all vary. Despite this, all previous golden ages have ended, whether it be because of external pressures or internal fracturing; too much hubris or too little wariness. Looking at seven of humanity's greatest civilizations -- ancient Athens, the Roman Republic, Abbasid Baghdad, Song China, Renaissance Italy, the Dutch Republic and the Anglosphere -- historian and commentator Johan Norberg seeks to distill their strengths and shortcomings in answering the question: how do we ensure that our current golden age doesn't end? As insightful as it is riveting, Peak Human is at once a paean to our incredible progress and a warning that we cannot afford to be complacent."--Publisher's description.